An Opportunity to Increase the Level of Zakat Funds Receipt in the Inisiatif Zakat Indonesia (IZI) Riau from the Quality of Accounting Information, Accountability, Financial Technology, and Credibility - Urniyanti, Rika; Nasrah, Hidayati; Suryadi, Nanda (IAIN Kudus, 2024)
Zakat is an important aspect that influences human economic behavior and overall economic development. The potential of zakat can be used as a means to obtain large amounts of funds which can be used to overcome community economic problems. In line with this urgency, this research aims to determine the influence of the quality of accounting information, accountability, financial technology (fintech), and credibility on the level of receipt of zakat funds at Laznas IZI Riau. Using quantitative methods, the sample was 312 muzakki. Samples were taken using the formula by Isaac and Michael. The research results showed that accountability, financial technology (fintech), and credibility have a positive and significant influence on the level of receipt of zakat funds at Laznas IZI Riau. However, the quality of accounting information did not have a positive and significant effect.